Pengembangan Firewall Mikrotik dalam Blocking Akses untuk Meningkatkan Keamanan Jaringan Kantor Desa Cibalandong Subang - Rahman, Taufik; Wardoyo, Rifqi Choiri (STMIK Sinar Nusantara, 2025)
Network security is a crucial aspect in protecting data and communications from external threats, especially in a village office environment that manages important information. This study aims to develop and implement a Mikrotik firewall to improve network security at the Cibalandong Village Office, Subang, with a focus on optimizing access blocking. The research methodology includes a literature study on the basic principles of firewalls and Mikrotik, analysis of specific needs of the Cibalandong Village Office, design and implementation of firewall configurations, and evaluation of system performance. The Mikrotik firewall configuration is designed to block unauthorized access while ensuring stable and efficient network connectivity. The test results show that the Mikrotik firewall successfully blocks unwanted access according to the rules applied, without reducing network performance. In addition, functional testing such as NAT, VPN, and QoS ensure that these features function as expected, and the system shows good recovery capabilities in the face of potential disruptions. Thus, the Mikrotik firewall proves to be an effective solution to improve network security at the Cibalandong Village Office. This study emphasizes the importance of implementing a proper network security system and shows that the Mikrotik firewall can be relied on to meet the needs of protection and access management in the context of a village office network. These findings support the use of Mikrotik firewall as an optimal tool to ensure network security and performance in similar environments.